Non-linear analysis of masonry infilled steel frame under in-plane loading using Multi Pier method - Mohammad Mosa Ahmadvand; Ahmad Maleki; Masoud Pourbaba (Case Studies in Construction Materials, 2025)
In the event of an earthquake, the in-plane stiffness, strength, and energy absorption capacity of the lateral load-bearing system could be affected by the presence of masonry infill walls. The complex interaction between infilled masonry walls and structural frames has been studied extensively. The present study introduces a novel method for analyzing masonry infilled steel frames, termed the Multi Pier (MP) approach, which utilizes truss elements exhibiting nonlinear softening behaviors. The basis of the model is to transfer the masonry infilled frame into an assemblage of piers and braces. In order to validate the results of the proposed method, eight different masonry infilled frames are analyzed in the non-linear static range. A strong correlation was observed between the experimental and MP Method results in terms of predicting the ultimate load, initial stiffness, and crack formation. Furthermore, the model has the capability to track the spreading and location of tensile and shear cracks at each stage of the loading process. Using the proposed method, parametric studies were conducted to study the effect of masonry infill aspect ratio, opening size, and shape on the load-bearing capacity of steel frames containing masonry infills. The results were in accordance with previous studies which further show the accuracy of the proposed method.